How to Manage Technical Debt in a Lean Startup - Nilsson, Hampus; Petersson, Linus (My University, 2013)
Startups are becoming ever more prominent in today’s world and the lean startup movement has shown a method to reach success through rapid development and prototyping. The effects this has on software quality and how it should be handled is a novel subject, the concept of technical debt has been known within the field Software Engineering for over a decade but there is very little research on how it is, or should be handled in startup contexts. This study aims to fill this void through interviewing nine startups companies about their technical debt issues. Simultaneously the researchers developed an internet startup project and evaluated the effectiveness of methods and software tools that can be used to manage technical debt. To address difficulties of discussing technical debt a new model for classifying debt named the Technical Debt Quadrant is presented. To solve the issue of managing technical debt in startups a list of concrete tips for managing technical debt and a matrix appellated the Debt Strategy Matrix that can be consulted in the different phases of a startup’s life was developed. The validity of these new solutions will need to be further evaluated in future studies to assess their usefulness. The new terms for referring to technical debt will be of use for both researchers and practitioners in the field of Software Engineering in the future. The strategies for managing technical debt can be used without the overhead associated with previous solutions by any startup to avoid long-term technical issues.
Keywords: Data- och informationsvetenskap; Computer and Information Science